(untitled) (Vietnam Journal of Community Medicine, 2024)
Curcuma L. is a large genus in the Zingiberaceae, many species have been used as spices, medicines, dyes, some plants are grown as ornamentals. Curcuma rangjued has been grown for many years in the Central Highlands provinces of Vietnam. Traditional medicine products from Curcuma rangjued are used to treat common diseases, such as respiratory tract infections, bronchitis, asthma, stomachache, skin inflammation. However, the plant is only locally known as scorpion turmeric, based on the shape of the rhizome of this plant, without a scientific name. It is unlike any turmeric species found in China, Laos, Cambodia and Vietnam with the following characteristics: inflorescences growing between leaf sheaths; abaxially green, usually with red patches on along side of midvein, fertile bract pale green; coma bract pale red, white towards basal. Notably, the rhizome has an intensely bitter taste. In this study, we identified and taxonomically described a new species of turmeric, Curcuma rangjued, contributing to the taxonomic diversity of Vietnam. Furthermore, pharmacological investigations revealed that the rhizome extract of C. rangjued exhibited significant inhibitory effects on the proliferation of four human cancer cell lines: A549 (lung carcinoma), MCF-7 (breast carcinoma), HT-29 (colorectal carcinoma), and SNU-1 (gastric carcinoma).